Ten-year clinical outcomes of everolimus- and biolimus-eluting coronary stents vs. everolimus-eluting bioresorbable vascular scaffolds—insights from the EVERBIO-2 trial - Bengueddache, Samir; Cook, Malica; Lehmann, Sonja; Arroyo, Diego; Togni, Mario; Puricel, Serban; Cook, Stephane (Frontiers in Cardiovascular Medicine, 2024)
Background Bioresorbable vascular scaffolds (BVSs) have been developed as a potential solution to mitigate late complications associated with drug-eluting metallic stents (DESs) in percutaneous coronary intervention for coronary artery disease. While numerous studies have compared BVSs to DESs, none have assessed clinical outcomes beyond 5 years. Objectives This study aimed to compare the 10-year clinical outcomes of patients treated with BVSs vs. DESs. Methods The EverBio-2 trial (Comparison of Everolimus- and Biolimus-Eluting Coronary Stents with Everolimus-Eluting Bioresorbable Vascular Scaffold) is a single-center, assessor-blinded, randomized controlled trial that enrolled 240 patients allocated in a 1:1:1 ratio to receive BVSs, everolimus-eluting stents, or biolimus-eluting stents (BESs). Clinical follow-up was scheduled for 10 years. Results Clinical follow-up was completed in 222 patients (93%) at the 10-year mark. The rate of device-oriented composite events (DOCE) was 28% in the DES group and 29% in the BVS group (p = 0.72) at 10 years. Similarly, the rate of patient-oriented composite events (POCE) was 55% in the DES group and 49% in the BVS group (p = 0.43) at 10 years. Notably, the rate of myocardial infarction (MI) within the target vessel was 5% in the BVS group and 0% in the BES group (p = 0.04), while the rate of any MI was 10% in the BVS group and 2% in the BES group (p = 0.04). In addition, the rate of Academic Research Consortium (ARC) possible stent thrombosis was 3% in the BVS group and 0% in the DES group (p = 0.04). Conclusions Over 10 years, the rates of clinical DOCE and POCE were similar between the BVS and DES groups but individual outcomes of stent thrombosis were higher (3%) in the BVS group compared to the DES group. Clinical Trial Registration ClinicalTrials.gov, identifier (NCT01711931).